2022
DOI: 10.1177/00048674221114782
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of attention deficit hyperactivity disorder medicine use in the era of new non-stimulant medicines: A population-based study among Australian children and adults (2013–2020)

Abstract: Background and aims: New therapeutic options such as lisdexamfetamine and guanfacine have recently become available for the treatment of attention deficit hyperactivity disorder. We described contemporary patterns of attention deficit hyperactivity disorder medicine use among children, adolescents and adults in Australia. Methods: This population-based study used dispensing data for a 10% random sample of Australian residents between July 2012 and December 2020. We estimated the annual prevalence and incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Population‐based information on longitudinal patterns of psychotropic agent dispensing for children and adolescents in Australia is limited. Evidence for increasing psychotropic use is restricted to particular types (antidepressants 11 or psychostimulants 12 ) or is based on analyses of general practice data 13 . The objective of our study was therefore to determine longitudinal patterns of dispensing of antidepressant, anxiolytic, antipsychotic, psychostimulant, and hypnotic and sedative medicines to children and adolescents in Australia during 2013–2021.…”
mentioning
confidence: 99%
“…Population‐based information on longitudinal patterns of psychotropic agent dispensing for children and adolescents in Australia is limited. Evidence for increasing psychotropic use is restricted to particular types (antidepressants 11 or psychostimulants 12 ) or is based on analyses of general practice data 13 . The objective of our study was therefore to determine longitudinal patterns of dispensing of antidepressant, anxiolytic, antipsychotic, psychostimulant, and hypnotic and sedative medicines to children and adolescents in Australia during 2013–2021.…”
mentioning
confidence: 99%
“…Despite the effectiveness and safety of treatment, especially medications, 12 ADHD among adults remains undertreated. 13 The IUIH Protocol represents a potentially effective model of care in the primary health sector. We are hopeful that with successful implementation, the rate of undiagnosed and untreated ADHD among Indigenous adults in South East Queensland will decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the effectiveness and safety of treatment, especially medications, 12 ADHD among adults remains undertreated. 13…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a substantial proportion of young individuals with ADHD continues to have impairing symptoms in adulthood, necessitating prolonged use of ADHD medication. Notably, studies have indicated a rising trend in the long-term use of ADHD medications, with approximately half of individuals using ADHD medication for over 5 years . Furthermore, evidence is lacking regarding how cardiovascular risk may vary based on factors such as type of CVD, type of ADHD medication, age, and sex .…”
Section: Introductionmentioning
confidence: 99%